High antiviral effect of TiO2·PL–DNA nanocomposites targeted to conservative regions of (−)RNA and (+)RNA of influenza A virus in cell culture - Levina, Asya S.; Repkova, Marina N.; Bessudnova, Elena V.; Filippova, Ekaterina I.; Mazurkova, Natalia A.; Zarytova, Valentina F. (Beilstein Journal of Nanotechnology, 2016)
Background: The development of new antiviral drugs based on nucleic acids is under scrutiny. An important problem in this aspect is to find the most vulnerable conservative regions in the viral genome as targets for the action of these agents. Another challenge is the development of an efficient system for their delivery into cells. To solve this problem, we proposed a TiO2·PL–DNA nanocomposite consisting of titanium dioxide nanoparticles and polylysine (PL)-containing oligonucleotides.Results: The TiO2·PL–DNA nanocomposites bearing the DNA fragments targeted to different conservative regions of (−)RNA and (+)RNA of segment 5 of influenza A virus (IAV) were studied for their antiviral activity in MDCK cells infected with the H1N1, H5N1, and H3N2 virus subtypes. Within the negative strand of each of the studied strains, the efficiency of DNA fragments increased in the direction of its 3’-end. Thus, the DNA fragment aimed at the 3’-noncoding region of (−)RNA was the most efficient and inhibited the reproduction of different IAV subtypes by 3–4 orders of magnitude. Although to a lesser extent, the DNA fragments targeted at the AUG region of (+)RNA and the corresponding region of (−)RNA were also active. For all studied viral subtypes, the nanocomposites bearing the DNA fragments targeted to (−)RNA appeared to be more efficient than those containing fragments aimed at the corresponding (+)RNA regions.Conclusion: The proposed TiO2·PL–DNA nanocomposites can be successfully used for highly efficient and site-specific inhibition of influenza A virus of different subtypes. Some patterns of localization of the most vulnerable regions in IAV segment 5 for the action of DNA-based drugs were found. The (−)RNA strand of IAV segment 5 appeared to be more sensitive as compared to (+)RNA.
Keywords: conservative regions; DNA fragments; H1N1, H5N1, and H3N2 subtypes of influenza A virus; TiO2·PL–DNA nanocomposites